Effect of Structured Physical Activity on Sleep–Wake Behaviors in Sedentary Elderly Adults with Mobility Limitations. Issue 7 (26th June 2015) - Vaz Fragoso, Carlos A.; Miller, Michael E.; King, Abby C.; Kritchevsky, Stephen B.; Liu, Christine K.; Myers, Valerie H.; Nadkarni, Neelesh K.; Pahor, Marco; Spring, Bonnie J.; Gill, Thomas M.; the Lifestyle Interventions; Independence for Elders Study Group
<x xml:space="preserve">Abstract</x> Objectives To evaluate the effect of structured physical activity on sleep–wake behaviors in sedentary community‐dwelling elderly adults with mobility limitations. Design Multicenter, randomized trial of moderate‐intensity physical activity versus health education, with sleep–wake behaviors prespecified as a tertiary outcome over a planned intervention period ranging from 24 to 30 months. Setting Lifestyle Interventions and Independence for Elders Study. Participants Community‐dwelling persons aged 70 to 89 who were initially sedentary and had a Short Physical Performance Battery score less than 10 (N = 1, 635). Measurements Sleep–wake behaviors were evaluated using the Insomnia Severity Index (ISI) (≥8 defined insomnia), Epworth Sleepiness Scale (ESS) (≥10 defined daytime drowsiness), and Pittsburgh Sleep Quality Index (PSQI) (>5 defined poor sleep quality) administered at baseline and 6, 18, and 30 months. Results The randomized groups were similar in terms of baseline demographic variables, including mean age (79) and sex (67% female). Structured physical activity resulted in a significantly lower likelihood of having poor sleep quality (adjusted odds ratios (aOR) for PSQI >5 = 0.80, 95% confidence interval (CI) = 0.68–0.94), including fewer new cases (aOR for PSQI >5 = 0.70, 95% CI = 0.54–0.89), than health education but not in resolution of prevalent cases (aOR for PSQI ≤5 = 1.13, 95% CI = 0.90–1.43). No significant intervention effects were observed for the ISI or ESS. Conclusion Structured physical activity resulted in a lower likelihood of developing poor sleep quality (PSQI >5) over the intervention period than health education but had no effect on prevalent cases of poor sleep quality or on sleep–wake behaviors evaluated using the ISI or ESS. These results suggest that the benefit of physical activity in this sample was preventive and limited to sleep–wake behaviors evaluated using the PSQI.